Customer Behavior as an Outcome of Social Media Marketing: The Role of Customer Experience on Football Jersey Sales on Tokopedia - Hakim, Adley Ajriel; Dhafi Iskandar, Muhammad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Football jerseys are highly sought-after merchandise in Indonesia, where 69% of the population are football enthusiasts. This study investigates the role of Customer Experience (CX) in driving Relationship Quality (RQ) and its subsequent impact on Purchase Intention (PUI), Loyalty Intention (LOI), and Participation Intention (PAI) for football jersey sales on Tokopedia. Using a quantitative approach, data were collected via an online survey of 254 Tokopedia users in Jakarta, analyzed through Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that CX significantly enhances RQ (coefficient: 0.909), which in turn positively influences PUI (0.901), LOI (0.915), and PAI (0.897). The study highlights the critical mediating role of RQ in translating social media marketing efforts into tangible consumer actions. These results offer practical implications for e-commerce platforms and marketers aiming to leverage CX and RQ to foster customer loyalty and engagement in Indonesia’s competitive digital marketplace. Limitations include focusing on Jakarta and specific age groups, suggesting avenues for future research across broader demographics and platforms.